Penggunaan Phet Colorado untuk Melatih Keterampilan Proses Sains pada Materi Bentuk Molekul: Penelitian - Annisa Sholehah Ayu Febriyanti; Muntholib; Dasianto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to train the science process skills of students in class X-4 SMA Brawijaya Smart School through the use of PhET Colorado simulation media on molecular shape material. This study was motivated by the low science process skills of students identified based on observation findings and written test results. The research was conducted using the Kurt Lewin model of classroom action method. Learning uses the "Molecule Shapes" simulation from PhET Colorado which provides explorative and interactive experiences to students in understanding molecular shapes. The results showed that the use of PhET simulation was able to improve six indicators of science process skills, namely observing, predicting, classifying, interpreting data, concluding, and modeling as well as strengthening students' conceptual understanding, especially in linking molecular shapes with the VSEPR model.